Dampak Teknologi Finansial terhadap Perkembangan Investasi Syariah di Era Digital - Al Hafidz; Aldin Nur Ainis Shofar; Serly Ikhtiari Krisdinar; Talita Choirunnisa; Sarpini Sarpini (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research explores the impact of financial technology (fintech) on the development of Islamic investment in the digital era. The study aims to analyze how fintech influences the accessibility and growth of Islamic investment products. Using a systematic literature review, this research examines various academic sources published between 2019 and 2024, focusing on countries with significant Islamic fintech developments such as Indonesia, Malaysia, and the Middle East. The findings indicate that fintech has enhanced public acceptance and participation in Islamic investment by offering more accessible and diverse financial products. However, regulatory challenges hinder the full potential of fintech in the Islamic finance sector. The research suggests that innovation in financial products and supportive regulations are key to fostering the growth of Islamic fintech. Additionally, further empirical research is recommended to explore the regulatory impacts and sustainability of Islamic fintech development across different regions.